Pierre Kropotkine et la loi naturelle de l’entraide : le fondement d’un droit nouveau ? - Claire Vachet (Clio@Themis)
The anarchist and geographer Peter Kropotkin refers to mutual aid to justify anarchism. He criticizes in his writings the state legal order and uses it as the basis for new anarchist social order and a new law. However, the anarchist’s thinking is confused : faced with the omnipotence of the natural law of mutual aid, we believe that law is superfluous in the anarchist social order that Peter Kropotkin calls for.